Aplikasi Pelacakan Alumni STMIK AKAKOM Berbasis Sistem Informasi Geografis - Iskandar, Edi; Sari, Dini Fakta (STMIK Palangkaraya, 2019)
Alumni is a product of an educational institution. The quality of the alumni shows the quality of the educational institution. The fact is increasingly felt, especially for college alumni. This is because alumni of college will directly come into contact with the world of work. Tracer study activity is one of the activities that have a very strategic value in the development of a college. STMIK Akakom is one of the universities in the city of Yogyakarta is required to always mempebaiki quality of education process accompanied by efforts to increase its relevance in the framework of global competition. In addition Tracer study is one effort that is expected to provide information to evaluate educational outcomes in STMIK Akakom. This information is used for further development in ensuring educational quality. This research produces alumni application of STMIK Akakom alumni by utilizing Geographic information system to map the location where alumni work, besides that it also displays alumni data in the form of year of admission, graduation year, long waiting time to work first after graduation